The Concept of Islamic Religious Education Abuddin Nata's Perspective - Aniiq Nazahah Rabbani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2022)
The purpose of this study was to determine the concept of Islamic religious education from the perspective of Abuddin Nata. This type of research uses library research methods that focus on studies and the study of a manuscript. This is done because the data sources obtained and used by researchers are in the form of literature. The conclusion of this study is to state that the Qur'an and al-Hadith are the main sources of Islamic education. The concept of Islamic education is monotheism which is imbued with divine and at the same time education in Islam as a form of worship. Education is essentially to increase human values ​​to a higher degree. In the beginning humans were one people and then multiplied and there were differences in ethnicity, skin color, and language and so on. National and language differences are not an obstacle to realizing the unity and oneness of mankind, basically education must be able to bring back one people.